2017
DOI: 10.1177/0885066617741470
|View full text |Cite
|
Sign up to set email alerts
|

Extended Versus Short-Course Corticosteroid Taper Regimens in the Management of Chronic Obstructive Pulmonary Disease Exacerbations in Critically Ill Patients

Abstract: A short-course corticosteroid taper in critically ill patients with AECOPD is associated with reduced hospital length of stay and decreased corticosteroid exposure without increased risk of treatment failure. A prospective randomized trial is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The difference in maximum systolic pressure was significant but not clinically relevant. Data from the literature promotes short courses with moderate doses of corticosteroids even for ICU patients [ 3 , 20 , 21 ] minimizing exposure to the drug. In a cohort of 17,239 patients, lower-doses of corticosteroid (methylprednisolone, ≤240 mg/d vs. >240 mg/d) were not associated with a significant reduction in mortality, but with reduced hospital and ICU length of stay, hospital costs, length of IMV, need for insulin therapy, and fungal infections [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in maximum systolic pressure was significant but not clinically relevant. Data from the literature promotes short courses with moderate doses of corticosteroids even for ICU patients [ 3 , 20 , 21 ] minimizing exposure to the drug. In a cohort of 17,239 patients, lower-doses of corticosteroid (methylprednisolone, ≤240 mg/d vs. >240 mg/d) were not associated with a significant reduction in mortality, but with reduced hospital and ICU length of stay, hospital costs, length of IMV, need for insulin therapy, and fungal infections [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 17,239 patients, lower-doses of corticosteroid (methylprednisolone, ≤240 mg/d vs. >240 mg/d) were not associated with a significant reduction in mortality, but with reduced hospital and ICU length of stay, hospital costs, length of IMV, need for insulin therapy, and fungal infections [ 21 ]. Overall, in these studies, critically ill patients admitted for AECOPD were treated with higher doses than the recommended dose for non-ICU patients [ 20 , 21 ]. The question of the optimal corticosteroid dose for ICU patients therefore remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also suggests that OCS improve lung function in ambulatory patients with COPD exacerbation and decrease the rate of hospitalizations, however, limited data on optimal corticosteroid dosage exist (80). A retrospective study in 151 patients with AECOPD admitted to the intensive care unit (ICU) indicated that the risk of treatment failure was similar in both extended-and short-course corticosteroid treatment groups, but the short-duration tapering group was associated with reduced length of hospital stay (81). In general, an equivalent dosage of 40-60 mg of prednisone for approximately 5 days is acceptable.…”
Section: Treatment Of Aecopdmentioning
confidence: 99%
“…They are considering the non-inferior clinical outcome in an acute episode of COPD in patients receiving corticosteroids for a shorter period at equivalent doses compared to a longer period, as well as the benefits of reduced adverse events, low cost, and increased compliance. No need to taper off; this approach is the best way to treat indoor and outdoor COPD patients 6,7 .…”
Section: Introductionmentioning
confidence: 99%